Electrophysiological mechanisms underlying hypoxia‐induced deficits in visual spatial and non‐spatial discrimination - Qiu, Qi; Lv, Pengpeng; Zhongshen, Yihao; Yuan, Fengjuan; Zhang, Xinjuan; Zhou, Xiuzhu; Li, Shanhua; Liu, Xiaonan; Zhang, Jiaxing (Physiological reports, 2021)
Impaired visual cognition in residents of hypoxic environment has been widely reported; however, the underlying electrophysiological mechanisms remain unclear. In this study, 23 college students underwent three sessions of a Clock task test before a 30‐day high‐altitude exposure (Test 1) and 1 week (Test 2) and 3 months (Test 3) after they returned to lowlands. The Clock task consists of a visual spatial angle and a visual non‐spatial color discrimination subtask. Simultaneously, electroencephalography (EEG) was recorded during the Clock task. The behavioral results showed that, compared with Test 1, accuracy in Test 2 was significantly decreased in both the Angle and Color tasks, and reaction time (RT) was significantly increased in the Angle task. The event‐related potentials results showed that, during both tasks amplitudes of the occipital N1 and P3 components during both tasks were significantly decreased in Test 2, compared with Test 1. Moreover, N1 amplitude was negatively correlated with RT and positively correlated with accuracy. Further time–frequency EEG analysis showed that theta power at occipital sites was significantly decreased in both tasks in Test 2, compared with Test 1, and was negatively correlated with RT in the Angle task. In Test 3, both the behavioral performance and EEG activity recovered to the baseline level in Test 1. These findings suggested that hypoxia impairs both visual spatial and visual non‐spatial discriminations, and these impairments can recover after subjects return to lowlands. Inhibition of brain electrophysiological activity in the visual cortex may explain the deficits in visual cognition. A first longitudinal electrophysiological study for high altitude (HA) visual cognitions. Both visual spatial and visual non‐spatial abilities impaired after HA exposure. Inhibition of event‐related potential N1 and P3 in visual cortex explains the visual impairment.